Symbiotic Routing in Future Data Centers - Abu-Libdeh, Hussam; Costa, Paolo; Rowstron, Ant; O'Shea, Greg; Donnelly, Austin (The ACM SIGCOMM Conference on Data Communication (SIGCOMM), 2010)
Building distributed applications that run in data centers is hard. The CamCube project explores the design of a shipping container sized data center with the goal of building an easier platform on which to build these applications. CamCube replaces the traditional switch-based network with a 3D torus topology, with each server directly connected to six other servers. As in other proposals, e.g. DCell and BCube, multi-hop routing in CamCube requires servers to participate in packet forwarding. To date, as in existing data centers, these approaches have all provided a single routing protocol for the applications. In this paper we explore if allowing applications to implement their own routing services is advantageous, and if we can support it efficiently. This is based on the observation that, due to the exibility offered by the CamCube API, many applications implemented their own routing protocol in order to achieve specific application-level characteristics, such as trading off higher-latency for better path convergence. Using large-scale simulations we demonstrate the benefits and network-level impact of running multiple routing protocols. We demonstrate that applications are more efficient and do not generate additional control traffic overhead. This motivates us to design an extended routing service allowing easy implementation of application-specific routing protocols on CamCube. Finally, we demonstrate that the additional performance overhead incurred when using the extended routing service on a prototype CamCube is very low.